Evaluation of Fertilizer Formulations on Yield and Quality of Malt Barley Varieties in Mau, Kenya - Sakwa , Brian; Ngode , Lucas; Anjichi , Victoria; Ochuodho , Julius (African Journal of Education,Science and Technology (AJEST), 2021)
Appropriate nutrition is essential for unlocking the yield potential of malt barley varieties and grains with malting quality within the required levels. Obtaining optimal yield, malting, and brewing quality of malt barley has been a major bottleneck in the brewing industry and seems not easy to obtain. A study was conducted in the Mau escarpment region to determine the influence of novel fertilizer formulations at different rates on the yield and quality of malt barley varieties in the Mau escarpment region. Balanced, soil informed fertilizer formulations (Baraka formulation 1 and 2) were developed then tried in two sites: Mau Narok and Olokurto to assess their influence yield, malting, and brewing quality of two malt barley varieties. The experiment was laid out in a split-plot arrangement in Randomized Complete Block Design with 3 replications. The varieties (Grace and Quench) were the main plots, fertilizer rates were the subplots (120 kg, 175 kg, 230 kg, and 290 kg/ha). Data was collected on yield and yield attributes, malting and brewing quality recorded then subjected to Analysis of Variance using R to determine the significant difference, whereas means were separated by the Duncan Multiple Range Test at a 5% level of significance. In this study, the varietal effects were significant in Olokurto but not in Mau in terms of yields; Grace was the better performing variety in Olokurto. 175 kg/ha was the optimal rate for both Baraka formulations. Both variety and the fertilizer rates had grains that met their malting and brewing quality requirements. The performances of the two fertilizer blends were at par with the standard control, however, Baraka formulation 1 was the best of the two blends and it can be used as alternatives for DAP fertilizer at the rate of 175 kg /ha. The fertilizer blends should however be tried more seasons to determine their stability.